2002
DOI: 10.1183/09031936.02.00271602
|View full text |Cite
|
Sign up to set email alerts
|

An 11-yr-old male with pneumonia and persistent airway obstruction

Abstract: Case reportAt the age of 4 yrs the male child suffered from a Wilms-tumour of the right kidney treated by polychemotherapy (SIOP No. 9 for stage 1 using actinomycin and vincristin) and surgical removal. A year later, abdominal pain occurred and a local relapse of the Wilms-tumour was diagnosed. Further diagnostics revealed infiltration into the liver, diaphragm, and the thoracic wall. In addition, three lung metastases were found. The child received polychemotherapy again (according to protocol SIOP 93/01 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…Recently, Kesrouani et al reported successful treatment of tracheal MEC by Argon plasma coagulation with no recurrence of the tumor after 5 years [4]. Histological grade, tumor staging, and complete tumor resection are important prognostic indicators [1618]. Moreover, Zhu et al demonstrated recently that the presence of MAML2 rearrangement within the tumor was associated with longer overall survival and disease-free survival in pulmonary MEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kesrouani et al reported successful treatment of tracheal MEC by Argon plasma coagulation with no recurrence of the tumor after 5 years [4]. Histological grade, tumor staging, and complete tumor resection are important prognostic indicators [1618]. Moreover, Zhu et al demonstrated recently that the presence of MAML2 rearrangement within the tumor was associated with longer overall survival and disease-free survival in pulmonary MEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, the tumor cells are located in the submucosa of the large bronchi and comprise of three components: Mucus-secreting, squamous and intermediate cells. [3467] These three cell types can be organized in to different patterns including glands, tubules, cysts, nests and solid areas. The mucus-secreting cells are usually large and have light blue mucinous cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Because no characteristic features distinguish these tumors from bronchogenic carcinoma and other benign lesions, bronchoscopy and biopsy are especially helpful in establishing the diagnosis (14,16). Mucoepidermoid carcinoma of the lung (formally called bronchial adenoma) consists 5% to 10% of these tumors (17,18). This tumor is a common salivary type of primary tumors in lung after adenoid cystic carcinoma (19).…”
Section: Discussionmentioning
confidence: 99%